3D printed gelatin-genipin scaffolds for temporomandibular joint cartilage regeneration. (27th August 2021) - Helgeland, Espen; Mohamed-Ahmed, Samih; Shanbhag, Siddharth; Pedersen, Torbjørn O; Rosén, Annika; Mustafa, Kamal; Rashad, Ahmad
Abstract: Gelatin has emerged as a biocompatible polymer with high printability in scaffold-based tissue engineering. The aim of the current study was to investigate the potential of genipin-crosslinked 3D printed gelatin scaffolds for temporomandibular joint (TMJ) cartilage regeneration. Crosslinking with genipin increased the stability and mechanical properties, without any cytotoxic effects. Chondrogenic differentiation of human bone marrow-derived mesenchymal stem cells (hBMSC) on the scaffolds were compared to cell pellets and spheres. Although hBMSC seeded scaffolds showed a lower expression of chondrogenesis-related genes compared to cell pellets and spheres, they demonstrated a significantly reduced expression of collagen (COL) 10, suggesting a decreased hypertrophic tendency. After 21 days, staining with Alcian blue and immunofluorescence for SOX9 and COL1 confirmed the chondrogenic differentiation of hBMSC on genipin-crosslinked gelatin scaffolds. In summary, 3D printed gelatin-genipin scaffolds supported the viability, attachment and chondrogenic differentiation of hBMSC, thus, demonstrating potential for TMJ cartilage regeneration applications.